Encyclopedia of Applied Plant Sciences:Vol-2. - Thomas, Brian;Ed. Murphy, Denis J;Ed (Elsevier Academic Press, 2003)
A multi-faceted reference work, the Encyclopedia of Applied Plant Sciences addresses the core knowledge, theories, and techniques employed by plant scientists, while also concentrating on applications of these in research and in industry. Plants influence all our lives as sources of sustenance, fuel and building materials. The Encyclopedia of Applied Plant Sciences is a comprehensive yet succinct publication that covers the application of current advances in the biological sciences, through which scientists can now better produce sustainable, safe food, feed and food ingredients, and renewable raw materials for industry and society. This three-volume set also covers the concerns over continuing advances in the application of knowledge in the areas of ecology and plant pathology, genetics, physiology, biochemistry and biotechnology, as well as the ethical issues involved in the use of the powerful techniques available to modern plant science. An invaluable reference, the Encyclopedia of Applied Plant Sciences will be an indispensable addition to the library of anyone involved in the study of plant sciences. The Encyclopedia of Applied Plant Sciences is available online on ScienceDirect. The print edition price for this reference work does not include online access. For more information on pricing for access to the online edition, please review our Licensing Options. The richness and authority of Elsevier reference works is now lent valuable functionality and accessibility through the online launch of Elsevier Reference Works on ScienceDirect. Features: Extensive browsing and searching across subject, thematic, alphabetical, author and cited author indexes - as applicable to the work Basic and advanced search functionality within volumes, parts of volumes, or across the whole work Ability to build, save and re-run searches as well as combine saved searches Internal cross-referencing between articles in the work, plus dynamic linking to journal articles and abstract databases, making navigation flexible and easy All articles are available as full-text HTML files, and as PDF files that can be viewed, downloaded or printed out in their original print format A dedicated Reference Works navigation tab and homepage on ScienceDirect to enable easy linking from your OPAC or library website For more information about the Elsevier Reference Works on ScienceDirect Program, please visit: http://www.info.sciencedirect.com/reference_works. Key Features * Comprehensively covers both the key theoretical and practical aspects of plant sciences * Edited and written by a distinguished international group of editors and contributors * Well-organized format provides for concise, readable entries, easy searches, and thorough cross-references * Presents complete up-to-date information on over 25 separate areas of plant science * Features many tables and figures, with a color plate section in each volume * New terms clearly explained in glossary sections of each article